Global Transcriptomic Changes Induced by Infection of Cucumber (Cucumis sativus L.) with Mild and Severe Variants of Hop Stunt Viroid - Xia, Changjian; Li, Shifang; Hou, Wanying; Fan, Zaifeng; Xiao, Hong; Lu, Meiguang; Sano, Teruo; Zhang, Zhixiang (Frontiers in Microbiology, 2017)
Fifteen years after transfer to hops, hop stunt viroid grapevine (HSVd-g) was replaced by HSVd-hop (HSVd-h), a sequence variant that contains changes at five different positions. HSVd-g54 is a laboratory mutant derived from HSVd-g that differs from its progenitor by a single G to A substitution at position 54. While infection by HSVd-h induces only mild stunting in cucumber (Cucumis sativus L.), HSVd-g54 induces much more severe symptoms in this indicator host. Comparison of transcriptome profiles of cucumber infected with HSVd-h or HSVd-g54 with those of mock-inoculated controls obtained by whole transcriptome shotgun sequencing revealed that many genes related to photosynthesis were down-regulated following infection. In contrast, genes encoding RNA-dependent RNA polymerase 1 (CsRDR1), especially CsRDR1c1 and CsRDR1c2, as well as those related to basal defense responses were up-regulated. Expression of genes associated with phytohormone signaling pathways were also altered, indicating that viroid infection initiates a complex array of changes in the host transcriptome. HSVd-g54 induced an earlier and stronger response than HSVd-h, and further examination of these differences will contribute to a better understanding of the mechanisms that determine viroid pathogenicity.